2021
DOI: 10.1088/1361-6552/ac03fb
|View full text |Cite
|
Sign up to set email alerts
|

How can GeoGebra support physics education in upper-secondary school—a review

Abstract: Recently, GeoGebra, a mathematics education software, has entered the scene of physics education; however, research on how the software can be used to support teaching and learning physics is limited and scattered. The aim of this article is to present a review of the current literature on how GeoGebra can be used to support physics education in upper-secondary schools. The general conclusion that comes from these studies is that GeoGebra is a user-friendly software that can be operated intuitively by teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…In contrast, some (f:14, 64%) used mobile and computersupported interactive applications such as PhET, Stellarium, Algebra, Tinkercad, and Physician. It is understood from the relevant literature that effective physics teaching is made by making use of various interactive applications (Jimoyiannis Komis, 2001;Karamustafaoğlu, 2012;Solvang & Haglund, 2021;Walsh, 2017). In addition, Özdemir & Çoramik (2021), in their research on optics, state that other applications such as Algodoo and PhET for physics lessons can be more effective by using them together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some (f:14, 64%) used mobile and computersupported interactive applications such as PhET, Stellarium, Algebra, Tinkercad, and Physician. It is understood from the relevant literature that effective physics teaching is made by making use of various interactive applications (Jimoyiannis Komis, 2001;Karamustafaoğlu, 2012;Solvang & Haglund, 2021;Walsh, 2017). In addition, Özdemir & Çoramik (2021), in their research on optics, state that other applications such as Algodoo and PhET for physics lessons can be more effective by using them together.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the physics teachers with more than twenty years of professional experience (f:6, 50%) and the majority of the teachers with less than twenty years of professional experience (f:8, 80%) stated that they used Algodoo or similar simulation programs in their lessons. In the literature, it is reported that teachers use simulation programs in the first years of their profession (Solvang & Haglund, 2021). It was found that almost all of the teachers working at the Science and Art Center (f:11, 91%) used simulation programs in their lessons or in preparing projects.…”
Section: Discussionmentioning
confidence: 99%
“…A meaningful advantage of the application is a broad international community building a rich reservoir of shared materials (e.g. [15,17,20,22,23]). It provides various tools like numerical solving of algebraic equations and Ordinary Differential Equations (ODE's) or simple animations.…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, this poor knowledge and skills place higher demands on the quality of the study materials prepared. The aim of this paper is to create a dynamic interactive construction of a thin converging and diverging lens in GeoGebra and to show the possibilities of using this software in teaching geometrical optics at secondary school (for review see [2]). Similar issues have been addressed in studies [3][4][5].…”
Section: Introductionmentioning
confidence: 99%